Modelagem em tempo real do erro sistemático das observáveis GPS devido à ionosfera - De Aguiar, Claudinei Rodrigues [UNESP]; Camargo, Paulo de Oliveira [UNESP] (My University, 2006)
Single frequency GPS receivers have been many used in GPS surveys. Among the several applications, one can mention those that are to obtain the receiver's antenna coordinates in real time. One of the main error sources to these applications is the ionosphere systematic error. In the FCT/UNESP a regional ionosphere model (Mod_Ion) was developed. It has been implemented to execute after collecting of GPS data. At real time application two improvements in the Mod_Ion were introduced, consisting of an alteration of the function of modeling and implementation of the Kalman Filter. The results of the experiments showed that the modifications were the most effective in the ionosphere systematic effect's corrections, providing a improvement in the accuracy of point positioning, of 90,75%, in period of the highest ionosphere activity.
Real time modeling of the systematic error in GPS observables due to ionosphere
Keywords: GPS; Ionosphere; Kalman filter; Pseudorange; ionosphere; numerical model; real time